Illness Perception of Asthma Patients in Compliance with Pharmaceutical Care - Lorensia, Amelia; Lisiska, Natalia (Faculty of Psychology, Universitas Surabaya, 2011)
Illness perceptions can affect patient’s self-management behavior, thus affecting asthma therapy outcomes. This study aims to test the correlation between asthma perception and the outcomes of the therapy. The design was a cross-sectional with purposive sampling technique. Data was obtained by direct interview using questionnaire and was presented descriptively, from 22 asthma patients. Results reveal significant differences between consequences, timeline, emotional response, understanding, and compliance. Illness perceptions of patients regarding the identity, cause of illness, and cure or control were appropriate, while concerning the conse- quences and timeline were still lacking. These shortcomings should be alleviated to support an optimal pharmaceutical care and improving the quality of life. Persepsi terhadap penyakit asma dapat memengaruhi perilaku manajemen-diri pasien, sehingga memengaruhi hasil terapinya. Studi ini bertujuan melihat korelasi antara persepsi terhadap penyakit asma dan hasil terapi. Metode yang dipakai adalah belah silang dan teknik sampling bertujuan. Data diperoleh dari 22 pasien asma melalui wawancara langsung dan pengisian kuesioner. Terdapat perbedaan yang bermakna antara konsekuensi, perjalanan penyakit, respons emosional, pengertian dan kepatuhan pada perawatan farmasetis. Persepsi pasien terhadap penyakitnya menyangkut identitas, penyebab penyakit, dan penyembuhan atau pengendalian sesuai, sedangkan masih kurang terhadap konsekuensi dan perjalanan penyakit. Hal-hal yang masih kurang inilah yang perlu diatasi sehingga rawatan farmasetikal bisa optimal dalam memperbaiki kualitas hidupnya.